Myelination may be impaired in neonates following birth asphyxia - Olivieri, Bianca (Neuroimage Clin, 2021)
BACKGROUND: Myelination is a developmental process that begins during the end of gestation, intensifies after birth over the first years of life, and continues well into adolescence. Any event leading to brain injury around the time of birth and during the perinatal period, such as birth asphyxia, may impair this critical process. Currently, the impact of such brain injury related to birth asphyxia on the myelination process is unknown. OBJECTIVE: To assess the myelination pattern over the first month of life in neonates with neonatal encephalopathy (NE) developing brain injury, compared to neonates without injury (i.e., healthy neonates and neonates with NE who do not develop brain injury). METHODS: Brain magnetic resonance imaging (MRI) was performed around day of life 2, 10, and 30 in healthy neonates and near-term/term neonates with NE who were treated with hypothermia. We evaluated myelination in various regions of interest using a T2* mapping sequence. In each region of interest, we compared the T2* values of the neonates with NE with brain injury to the values of the neonates without injury, according to the MRI timing, by using a repeated measures generalized linear mixed model. RESULTS: We obtained 74 MRI scans over the first month of life for 6 healthy neonates, 17 neonates with NE who were treated with hypothermia and did not develop brain injury, and 16 neonates with NE who were treated with hypothermia and developed brain injury. The T2* values significantly increased in the neonates with NE who developed injury in the posterior limbs of the internal capsule (day 2: p < 0.001; day 10: p < 0.001; and day 30: p < 0.001), the thalami (day 2: p = 0.001; day 10: p = 0.006; and day 30: p = 0.016), the lentiform nuclei (day 2: p = 0.005), the anterior white matter (day 2: p = 0.002; day 10: p = 0.006; and day 30: p = 0.002), the posterior white matter (day 2: p = 0.001; day 10: p = 0.008; and day 30: p = 0.03), the genu of the corpus callosum (day 2: p = 0.01; and day 10: p = 0.006), and the optic radiations (day 30: p < 0.001). CONCLUSION: In the neonates with NE who were treated with hypothermia and developed brain injury, birth asphyxia impaired myelination in the regions that are myelinated at birth or soon after birth (the posterior limbs of internal capsule, the thalami, and the lentiform nuclei), in the regions where the myelination process begins only after the perinatal period (optic radiations), and in the regions where this process does not occur until months after birth (anterior/posterior white matter), which suggests that birth asphyxia, in addition to causing the previously well-described direct injury to the brain, may impair myelination.